Isolation of viable but nonculturable Vibrio cholerae O1 from environmental water samples in Kolkata, India, in a culturable state. Issue 2 (18th February 2014) - Senoh, Mitsutoshi; Ghosh‐Banerjee, Jayeeta; Mizuno, Tamaki; Shinoda, Sumio; Miyoshi, Shin‐ichi; Hamabata, Takashi; Nair, G. Balakrish; Takeda, Yoshifumi
Abstract Previously, we reported that viable but nonculturable (VBNC) Vibrio cholerae was converted into a culturable state by coculture with several eukaryotic cell lines including HT‐29 cells. In this study, we found that a factor converting VBNC V. cholerae into a culturable state (FCVC) existed in cell extracts of eukaryotic cells. FCVC was nondialyzable, proteinase K‐sensitive, and stable to heating at <60°C for 5 min. We prepared thiosulfate citrate bile salts sucrose (TCBS) plates with FCVC (F‐TCBS plates). After confirming that VBNC V. cholerae O1 and O139 formed typical yellow colonies on F‐TCBS plates, we tried to isolate cholera toxin gene‐positive VBNC V. cholerae from environmental water samples collected in urban slum areas of Kolkata, India and succeeded in isolating V. cholerae O1 El Tor variant strains harboring a gene for the cholera toxin. The possible importance of VBNC V. cholerae O1 as a source of cholera outbreaks is discussed.